ChemInform Abstract: Thermodynamically Driven, syn‐Selective Vinylogous Aldol Reaction of Tetronamides. Issue 40 (16th September 2016) - Karak, Milandip; Barbosa, Luiz C. A.; Acosta, Jaime A. M.; Sarotti, Ariel M.; Boukouvalas, John
Abstract: The aldol reaction between N‐monoarylated tetronamides and various aryl, hetaryl or alkyl aldehydes is examined.